1978
DOI: 10.1037/0096-1523.4.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Functional representations common to visual perception and imagination.

Abstract: Subjects determined whether probe dots appearing in component squares of a 5 X 5 grid fell on a figure that, depending on the condition, was (a) visually presented as a pattern of darkened squares, (b) only remembered from a preceding presentation of such a pattern, or (c) imaginally generated from a verbal code. The speed and accuracy of the responses to the probes as well as the functional dependencies of the reaction times on structural variables were essentially the same whether the figural pattern was ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 36 publications
(26 reference statements)
3
86
1
Order By: Relevance
“…So it seems that the mental image of a cube does not explicitly represent some of the relationships that are perceptually available, nor does it allow them to be easily inferred. This observation may appear to conflict with the claim by Podgorny and Shepard (1978) that mental images are very similar to percepts. However, their view is quite compatible with the evidence if one allows that there may be several different ways of representing the spatial structure of an object, and that at any moment only one representation can be entertained.…”
Section: The Effect Of Perceiving the Objectcontrasting
confidence: 55%
“…So it seems that the mental image of a cube does not explicitly represent some of the relationships that are perceptually available, nor does it allow them to be easily inferred. This observation may appear to conflict with the claim by Podgorny and Shepard (1978) that mental images are very similar to percepts. However, their view is quite compatible with the evidence if one allows that there may be several different ways of representing the spatial structure of an object, and that at any moment only one representation can be entertained.…”
Section: The Effect Of Perceiving the Objectcontrasting
confidence: 55%
“…This study used a task devised by Podgorny and Shepard (1978) where subjects were asked to visualize block letters in grids and decide whether a probe mark (presented on an empty grid) would have fallen on the letter if this were actually present. Kosslyn et al had observed prior to the experiment how individuals wrote each block letter and selected those that were drawn in a consistent way.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these concerns generation effects (Posner, 1975), which make it necessary to assume that primary processing can be initiated subsequent to initial stimulus identification, for example, by a deliberate decision to imagine an alternative form of the presented stimulus. When generation has been examined in relation to repetition priming between translations (Kirsner et al, 1984, Experiment 2), the results have suggested that generation yields effects that are not readily distinguished from normal stimulus identification, as has been shown for a variety of perceptual tasks (e.g., Farah, 1985;Finke, 1980;Podgorny & Shepard, 1978). The second qualification concerns the possibility that secondary processing is, like primary processing, sensitive to the relationship between study and test conditions (Tulving, 1983), except that in this case secondary processing can be expected to reflect the extent to which the same secondary processes are invoked during study and test.…”
Section: Word and Picture Identification 405mentioning
confidence: 99%